Application of organic fertilisers on natural stand bamboos for sustainable management in Peninsular Malaysia - Mohamed, Azmy; Wahab, Razak; Hashim, Waqar S.; Sulaiman, Othman (2004)
This paper highlights research on the influence of three organic fertilisers (chicken dung, palm oil mill effluent and peat materials specially made for fertilisers) on the number of new shoots, the diameter at breast height, the height of the culms and the number of culms. Especially the number of new shoots and the diameter at breast height are positively influenced, which is promising for commercial purposes.